FEMALE ENGLISH STUDENTS (FES) LANGUAGE LEARNING STRATEGIES IN THE DIGITAL ERA - Sulistiana Ulpa; Syarifuddin Dollah; Samtidar Samtidar (JTechLP: Journal of Technology in Language Pedagogy, 2023)
The objective of this research was to find out what strategies female English students utilize in their English learning in the digital era by using ICT namely technology tools and social media applications. This research took place at the State University of Makassar, Faculty of Language and Literature. The participants of this research were female students of the English Education Study Program class 2021. The researcher used a case study qualitative method with a purposive sampling technique to select the participants. The instrument of this research was questionnaire and interview. Based on the result of the questionnaire and interview, The researcher found that female English students’ strategies for improving their listening skills were watching Western movies, watching video gaming on YouTube, watching English lesson videos, watching TikTok content from native speakers/foreigners, listening to English song, and doing listening exercises; in improving their speaking skills were speaking English with friends by chatting, watching western movies then practice it, watching English lesson videos, watching English videos on TikTok from overseas content creator and learning vocabulary; in improving their reading skill were reading online comics, reading e-books/articles in English, reading movie subtitles, and reading captions and comments on Twitter; in improving their writing skills were doing essay writing assignments, writing social media status, chatting on WhatsApp, and practice writing on Grammarly.